Epistemological Analysis of the Integration of the Merdeka Curriculum and Deep Learning Technology in Islamic Education in the Digital Era - Muhammad Nadhif Syuhada; Helmiati Helmiati; Hariza Hasyim (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
The transformation of education in the digital era has shifted the paradigm from conventional learning systems toward more adaptive, personalized, and technology-based models. This study aims to analyze the epistemological integration between the Merdeka Curriculum and deep learning technology within the development of Islamic education in the digital age. The research employed a library research method using content analysis of academic books, scholarly articles, and relevant policy documents. The findings reveal that the integration offers significant opportunities, including enhanced learning personalization, strengthened spiritual digital literacy, and pedagogical efficiency through adaptive learning systems. However, the study also identifies several epistemological and ethical challenges, such as value bias within algorithms, the risk of reducing spiritual dimensions into computational data, and limitations in digital competence among Islamic education teachers and institutional infrastructures. Epistemologically, the integration of technology in Islamic education must remain grounded in the principles of tawhid, adab, and maq??id al-tarbiyah to prevent fragmentation between knowledge and values. This study contributes theoretically by proposing an epistemological integration framework between curriculum and technology, and practically by offering insights for developing Islamic pedagogy that remains ethically and spiritually rooted while adapting to digital advancements.